Exploiting the polyphenolic potential of honey in the prevention of chronic diseases - Wani Suhana Ayoub; Ritu; Insha Zahoor; Aamir Hussain Dar; Salma Farooq; Tanveer Ahmad Mir; Tariq Ahmad Ganaie; Shivangi Srivastava; Vinay Kumar Pandey; Aayeena Altaf (Food Chemistry Advances, 2023)
For a person to remain healthy, a powerful immune system is highly recommended. Everybody should include particular food in their diet that can boost their immune system. Nature has been bestowed with the huge treasure of plants and trees whose various portion; each contain unique compounds that can strengthen the immune system. Honey has long been selected as a pure unique product for its therapeutic potential. Due to their strong anti-inflammatory and antioxidant capabilities, phenolic acids and flavonoids have significant impact on human health. By altering many biochemical processes involved in cellular proliferation, honey exhibits antibacterial capabilities and anticancer actions against diverse tumour types. The decrease in blood levels of glucose, fructosamine, and glycosylated haemoglobin is another antidiabetic benefit that has been noted. Additionally, honey has health-promoting benefits on the respiratory system against asthmatic and bacterial infection, the duodenal system, the blood-vascular system, where it primarily protects the oxidation of low-density lipoproteins, and the brain system. This review focusses on the exploitation of polyphenolic compounds present in honey.